Effect of Prolonged Exposure Cherry Leaf Extract (Muntingia calabura) on The Death Larvae Aedes aegypti: Effect of Prolonged Exposure Cherry Leaf Extract (Muntingia calabura) on The Death Larvae Aedes aegypti - Hajrah Hidriya (Politeknik Unggulan Kalimantan, 2024)
Dengue Fever (dengue) is an epidemic disease that occurs every year in Indonesia. Several solutions have been used by the community since the past until now in overcoming the outbreak of dengue disease, through mosquito eradication by fogging, using the method of draining, closing, and burying mosquito nests and Aedes aegypti larvae in stagnant water. Another alternative is needed, use of vegetable insecticides or environmentally friendly vector control, making larvicide from plant extracts. Kersen plant (Muntingia calabura) is one type of plant that has the potential to be developed as a vegetable insecticide. This study aims to determine the effect of prolonged exposure to Kersen extract (Muntingia calabura) on the death of Aedes aegypti larvae. The procedure in this study includes 4 processes, Kersen Leaf Sampling (Muntingia calabura), Making Kersen Leaf Extract (Muntingia calabura), Breeding Aedes aegypti mosquito larvae and Test of the Effect of Long Exposure to Kersen Leaf Extract (Muntingia calabura). The efficiency of the effect of prolonged exposure on the death of larvae is within 2 hours. As for the effectiveness of long exposure time to the death of larvae there is at a time of 24 hours. This suggests that the length of exposure time had an influence on the mortality of Aedes aegypti larvae.